PEMBUATAN PETA SITUASI SKALA 1:500 DUSUN BANYURIPAN DESA BANYURIPAN KECAMATAN BAYAT KABUPATEN KLATEN PROVINSI JAWA TENGAH - , FAJAR SURYA LESMANA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This final report explains about surveying and land mapping to produce spatial data information from the Earth's surface. Spatial data include spot height and planimetric detail which are derived from surveying of the earth's surface presented on the map. The method used is the manufacture of map control framework which consists of Horizontal Control Surveys and Vertical Control Surveys, planimetric detail and spot height measurements, and also digital mapping. The result obtained is the situation map presenting the spatial data on the Earth's surface, Banyuripan village, Bayat sub-district, Klaten district, Central Java province by using a scale of 1:500 in UTM (Universal Transverse Mercator) projection system.